L‐Citrulline ameliorates pathophysiology in a rat model of superimposed preeclampsia. (26th January 2022) - Man, Andy W. C.; Zhou, Yawen; Lam, Uyen D. P.; Reifenberg, Gisela; Werner, Anke; Habermeier, Alice; Closs, Ellen I.; Daiber, Andreas; Münzel, Thomas; Xia, Ning; Li, Huige
Abstract : Background and Purpose: Preeclampsia, characterized by hypertension, proteinuria and restriction of fetal growth, is one of the leading causes of maternal and perinatal mortality. So far, there is no effective pharmacological therapy for preeclampsia. The present study was conducted to investigate the effects of supplementation with l ‐citrulline in Dahl salt‐sensitive rats, a model of superimposed preeclampsia. Experimental Approach: Parental Dahl salt‐sensitive rats were treated with l ‐citrulline (2.5 g·L −1 in drinking water) from the day of mating to the end of lactation period. Blood pressure was monitored throughout pregnancy and markers of preeclampsia were assessed. Endothelial function of the pregnant Dahl salt‐sensitive rats was assessed by wire myograph. Key Results: In Dahl salt‐sensitive rats, l ‐citrulline supplementation significantly reduced maternal blood pressure, proteinuria and levels of circulating soluble fms‐like tyrosine kinase 1. l ‐Citrulline improved maternal endothelial function by augmenting the production of nitric oxide in the aorta and improving endothelium‐derived hyperpolarizing factor‐mediated vasorelaxation in resistance arteries. l ‐Citrulline supplementation improved placental insufficiency and fetal growth, which were associated with an enhancement of angiogenesis and reduction of fibrosis and senescence in the placentas. In addition, l ‐citrulline down‐regulated genes involved in the TLR4 and NF‐κB signalling pathways. Conclusion and Implications: This study shows that l ‐citrulline supplementation reduced gestational hypertension and improved placentation and fetal growth in a rat model of superimposed preeclampsia. l ‐Citrulline supplementation may provide an effective and safe therapeutic strategy for preeclampsia that benefits both the mother and the fetus.